Constitutional Law System in Indonesia and Its Comparison with Other Legal Systems - Yunus, Nur Rohim; Siagian, Amrizal; Zein, Fitriyani (SALAM: Jurnal Sosial dan Budaya Syar-i, 2022)
Constitutional law is characterized in a broad sense as the legal laws controlling state structures, the interaction between vertical and horizontal state instruments, and the position of citizens and their human rights. Nevertheless, there are variations in the techniques and methods of applying the state system, in addition to the standard regulations that serve as the state's fundamental standards. This study employed a qualitative research strategy with a comparative study design. According to the findings of the study, the aims of the constitutional law systems of many nations are comparable. In contrast, Indonesia's legal system is founded on Pancasila and the Constitution of 1945 and seeks fairness for all its citizens. In Indonesia, the constitutional legal system recognizes legal plurality, Islamic law, and customary law. This is not found in other countries legal systems.Keywords: Legal System; State Administration; Legal Comparison Abstract:Hukum Tata Negara dalam pengertian umum diartikan sebagai sekumpulan peraturan hukum yang mengatur organisasi dari negara, hubungan antar alat perlengkapan negara dalam garis vertikal dan horizontal, serta kedudukan warga negara dan hak-hak asasinya. Namum dalam aplikasinya, terdapat perbedaan cara dan metode pelaksanaan sistem bernegara, selain terikat pada aturan baku yang menjadi landasan utama sebagai norma dasar suatu negara. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian kualitatif dengan pendekatan comparative studies. Hasil penelitian menyatakan bahwa ada kesamaan tujuan pada sistem hukum tata negara pada beberapa negara. Namun pada negara Indonesia, sistem hukumnya berdasarkan Pancasila dan UUD 1945 serta mencita-citakan keadilan bagi seluruh rakyatnya. Sistem hukum tata negara di Indonesia mengakui adanya pluralisme hukum, hukum Islam, dan hukum adat. Hal inilah yang tidak terdapat pada sistem hukum negara lain.Kata Kunci: Sistem Hukum; Tata Negara; Perbandingan Hukum